The Success of easyJet and Other Low Cost Airlines is Due to Their Focus on Pursuing A Pure Low Cost Strategy and the Subsequent Ruthless and Effective Management of their Value Chain - Shrager, James (2007)
Using theories by Michael Porter on competitive advantage, generic strategies and the value chain along with data obtained from the Civil Aviation Authority for easyJet and BMI British Midland this study examines what factors have contributed to the success of easyJet and the other low cost airlines. The assertion is that easyJet and other low cost airlines have been successful due to their focus on a pure low cost strategy achieved through the ruthless and effective management of their value chain. After refining Porter's value chain to better fit the airline industry in the UK an analysis of cost and operational data for easyJet and BMI for the years 2001 and 2006 was carried out. The results obtained were significant with the data showing that easyJet manages to operate at costs that are between 55% and 65% of BMI's. These cost savings are achieved through a few fundamental principles that underlie the low cost airline model, these being high aircraft utilisation achieved through clever timetabling and fast turnarounds, high load factors, and ruthless cost control. The final part of the study evaluates whether, in my opinion, the low cost airline industry is sustainable in the UK and after careful consideration of arguments for and against the sustainability I conclude that as long as the airlines stick to the key underlying principles then the model is sustainable.